PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PADA PRODUK PARFUM DI TOKO 69-COLLECTION SANGATTA - Andi Mursalin (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2021)
The purpose of this study was to determine and analyze the effect of product quality and brand image on consumer buying interest in perfume products at the 69-collection Sangatta store. The population in this study were consumers of the 69-Collection Sangatta Perfume Shop, the authors used the simple incidental method while the number of samples taken using the Rao Purba formula was 43 respondents. Data was taken using a questionnaire which was measured using a Likert scale. This study uses multiple linear regression analysis with the help of SPSS version 26 program. The results of the partial study show that the product quality variable (X₁) has a significant effect on consumer buying interest, the brand image variable (X₂) has a significant effect on consumer buying interest, buying interest variable (Y) has a significant effect on product quality and brand image then simultaneously variable product quality and brand image have a significant effect on consumer buying interest at 69-Collection Sangatta Perfume Shop. The contribution of product quality and brand image variables to consumer buying interest at 69-Collection Sangatta Perfume Shop in this study was 76.6%.